Competitive Mooting: An Opportunity to Build Resilience Skills for Legal Practice - Louise Parsons (Bond University, 2018)
Competitive mooting is highly suitable for teaching law students to be prepared for legal practice. In particular, competitive mooting as experiential learning in a mock dispute resolution setting provides a unique pedagogical tool that is ideally suited to the development of resilience in law students. Developing resilience in law students is therefore important for their future career practice. Although competitive mooting can spontaneous develop resilience, this article draws on Positive Psychology and proposes some strategies and practices that moot coaches can use to assist competitive moot teams to develop resilience and learn resilience skills with a view to legal practice. It includes a 'nutshell version' of some practical tips for moot coaches such as the focus on a growth mind-set, the importance of focussing on strengths and positivity, effective feedback, the ABCD formula and reflective practice.